Pengentasan Kemiskinan melalui Pembinaan UKM Bidang Perikanan Di Kawasan Pesisir Desa Sekotong Tengah Kabupaten Lombok Barat - Masrun, Masrun; Yuniarti, Titi; Suprianto, Suprianto (Jurnal Ekonomi dan Bisnis, 2018)
The Special Purpose of this study is expected to form a Program for the Development of local potential based SMEs to improve the skills of entrepreneurs by being motivated to try, be creative and innovate in carrying out their business activities. With increased skills will be able to improve the quality and quantity of the results of his business so that it will bring increased income and their welfare in order to alleviate poverty. The research was conducted by field survey method in the coastal area of ??Sekotong Tengah Village, West Lombok Regency. This activity is to identify opportunities and business feasibility of micro small entrepreneurs. Furthermore, the formation of SME Development Program can be formed in order to solve the problems it faces. From this activity, it is expected that UKM entrepreneurs can improve the quality and quantity of their business results so that it will encourage increased income. Increase the income of target entrepreneurs through increased production, quality of production and selling prices on the market. From the results of the study showed that of the four businesses analyzed, economically beneficial and also superior / developed temporarily in the coastal area of ??Sekotong Tengah Village, namely shrimp paste, goat, fish trade and crab business. The SME coaching program can be realized, showing: a). the role of the government in capital assistance other than banking institutions and skills assistance, b). SME entrepreneurs need to form groups / institutions as a medium for SMEs, c). the existence of a business partner to assist in the marketing and processing of production